A study on the causes of the destruction of the high pressure hoses during operation and cyclic tests - I. V. Borisovets; T. P. Kurenkova (Литьë и металлургия)
High pressure hose (HPH) is a flexible pipeline for the transportation of special hydraulic and motor fluids based on mineral oil, liquid fuel, grease or water emulsion under pressure, to transfer the working force. Structurally, the sleeve is two or more rubber tubes placed one into the other, reinforced with metal braids or coils, equipped with connecting fittings [1]. HPH is characterized by a sufficiently high flexibility in combination with the ability to withstand significant pressure.In cases of premature failure of high-pressure hoses during cyclic or impulse tests, the cause of the nonconformity must be determined. The article describes the main stages of the study of defective high-pressure hoses in determining the cause of their failure and provides examples of studies using visual, metallographic, electron microscopic methods of analysis in the metallographic laboratory of OJSC «BSW – Management Company of Holding «BMC».